2015
DOI: 10.1038/srep08604
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-23 promotes the epithelial-mesenchymal transition of oesophageal carcinoma cells via the Wnt/β-catenin pathway

Abstract: As the eighth most common malignant tumour worldwide, oesophageal cancer (OC) is often diagnosed during the metastasis of its advanced stage. Interleukin (IL)-23 is an immunomodulatory cytokine that has recently been identified as a cancer-associated factor. However, the role of IL-23 in the evolution of OC remains unclear. In the present study, we found that IL-23 was significantly expressed in the tumours of OC patients suffering metastasis and demonstrated that IL-23 contributed to epithelial-mesenchymal tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 37 publications
3
45
1
2
Order By: Relevance
“…In addition to these strategies, we suggest that the IL23-producing tumor-mediated conversion from ILC1 into ILC3 is a novel strategy of tumors that favors tumor progression and expansion in the TME. Similar to lung cancer, SqCCs in the esophagus also express IL23, contributing to the epithelialmesenchymal transition via the Wnt/b-catenin pathway (33). Thus, these findings suggest that IL23 produced by SqCCs has diverse effects on tumorigenesis and progression by regulating intrinsic tumor biology and cross-talk with extrinsic immune cells, which suggests that the IL23-ILC3 axis may be a therapeutic target for IL23-producing SqCCs.…”
Section: Discussionmentioning
confidence: 81%
“…In addition to these strategies, we suggest that the IL23-producing tumor-mediated conversion from ILC1 into ILC3 is a novel strategy of tumors that favors tumor progression and expansion in the TME. Similar to lung cancer, SqCCs in the esophagus also express IL23, contributing to the epithelialmesenchymal transition via the Wnt/b-catenin pathway (33). Thus, these findings suggest that IL23 produced by SqCCs has diverse effects on tumorigenesis and progression by regulating intrinsic tumor biology and cross-talk with extrinsic immune cells, which suggests that the IL23-ILC3 axis may be a therapeutic target for IL23-producing SqCCs.…”
Section: Discussionmentioning
confidence: 81%
“…Tumor infiltration by the proinflammatory Th17 T cells is associated with increased Th17‐associated cytokines IL‐23, IL‐17, IL‐1β, and IL‐6. In esophageal cancer, IL‐23 expression in the primary tumor relates to the presence of nodal and distance metastases (Chen et al ., ). In vitro , treatment of esophageal cancer cell lines with recombinant IL‐23 induces EMT‐like changes characterized by loss of E‐cadherin and de novo vimentin expression (Chen et al ., ).…”
Section: Emt and Soluble Factors Of Inflammationmentioning
confidence: 97%
“…In esophageal cancer, IL‐23 expression in the primary tumor relates to the presence of nodal and distance metastases (Chen et al ., ). In vitro , treatment of esophageal cancer cell lines with recombinant IL‐23 induces EMT‐like changes characterized by loss of E‐cadherin and de novo vimentin expression (Chen et al ., ). The signaling pathways in these cells comprise activation of the Wnt/β‐catenin pathway, subsequent GSK‐3β stabilization, which finally triggers Slug and Snail1 expression (Fig.…”
Section: Emt and Soluble Factors Of Inflammationmentioning
confidence: 97%
“…1g). We have previously suggested that aberrant IL-23 expression enhances the activity of EMT in ESCCs [14]. Therefore, IL-23 mediates the trans-differentiation not only by affecting the accumulation of stem-like makers but also by directionally inducing the expression of stemness-related genes in IL-23R + ESCCs.…”
Section: Resultsmentioning
confidence: 99%